Strategi Pemimpin pada Lembaga Pendidikan Islam dalam Meningkatkan Mutu Pendidikan Islam di Era Pandemi Covid 19 - Jumiati Jumiati; Anita Ariani; Mariyatul Norhidayati; St Rahmah (Al-Hiwar : Jurnal Ilmu dan Teknik Dakwah, 2022)
This article was compiled to find out how the strategy of leaders in Islamic educational institutions in improving the quality of learning in the era of the covid 19 pandemic. Through the literature study that has been carried out, it was found that the strategy of Leaders at Islamic Educational Institutions in improving the Quality of Learning in the Era of the Covid-19 Pandemic is by maintaining the professionalism of teachers and even improve their quality so that they can still provide quality learning even through online. In addition, the leader always monitors educational developments during the pandemic and seeks to maximize his own role as a leader, especially in terms of learning quality management, so as to obtain an increase in the quality of learning at Islamic Educational Institutions even during the Covid 19 pandemic era.